Composition and structure of high temperature dairy fouling. (January 2016) - Hagsten, Carin; Altskär, Annika; Gustafsson, Stefan; Lorén, Niklas; Hamberg, Lars; Innings, Fredrik; Paulsson, Marie; Nylander, Tommy
Graphical abstract: Highlights: Calcium phosphate rich dairy fouling with a clear crystalline structure. Clear structural variation in the heterogeneous fouling structure. Chemical composition show a spatial variation with distance to the heated surface. Abstract: The fouling structure and composition is dependent on the product, but also on the heating process applied to it. The structure will have profound effect on the cleaning process and the down time in the production plant. Here, the structure of high temperature (137 °C) milk fouling has been investigated, which so far has not been sufficiently studied in a systematic way. This particular fouling has a high content of the mineral calcium phosphate and a relatively low concentration of protein. Wide angle X-ray diffraction (WAXD) reveals a crystalline structure of calcium phosphate in agreement to the chemical analysis of the bulk layer. Microscopic investigations visualize the heterogeneous structure and energy dispersive X-ray spectroscopy (EDX) shows a spatial variation of the elements through the radius of the sample.